Social movements thinking for managing change in large-scale systems. Issue 5 (11th June 2020) - Holton, Judith A.
Abstract : Purpose: This study explores the efficacy of social movements thinking for mobilizing resources toward sustainable change in large-scale systems such as health and social services. Design/methodology/approach: The study proceeds from a critical realist perspective employing a qualitative multi-case study approach. Drawing on the tenets of grounded theory (i.e. constant comparative analysis and theoretical sampling), data from semi-structured interviews and field notes were analyzed to facilitate theoretical integration and elaboration. Findings: One case study explores the emergence of social movements thinking in mobilizing a community to engage in sustainable system change. Data analysis revealed a three-stage conceptual framework whereby building momentum for change requires a fundamental shift in culture through openness and engagement to challenge the status quo by acknowledging not only the apparent problems to be addressed but also the residual apathy and cynicism holding the system captive to entrenched ideas and behaviors. By challenging the status quo, energy shifts and momentum builds as the community discovers shared values and goals. Achieving a culture shift of this magnitude requires leadership that is embedded within the community, with a personal commitment to that community and with the deep listening skills necessary to understand and engage the community and the wider system in moving forward into change. This emergent conceptual framework is then used to compare and discuss more intentional applications of social movements thinking for mobilizing resources for large-scale system change. Originality/value: This study offers a three-stage conceptual framework for mobilizing community/system resources toward sustainable large-scale system change. The comparative application of this framework to more intentional applications of social movements thinking to planned change initiatives offers insights and lessons to be learned when large-scale systems attempt to apply such principles in redesigning health and social service systems.